Optimization of Service and Quality to Maintain Customer Loyalty in The Plastic Cup Printing Industry - Darmawan, Andrianti Rahayu; Prameka, Adelia Shabrina (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to evaluate the business conditions of CV Bersama Jaya, a food and beverage packaging printing company, and to formulate strategic development plans to overcome declining sales performance and improve business sustainability. Design/Methodology/Approach – This study employs a qualitative descriptive research and development approach. Data were collected through observations and interviews with the business owner. A comprehensive business analysis was conducted covering production, human resources, market conditions, marketing strategies, financial aspects, and external factors. SWOT analysis was applied to identify key business challenges and formulate appropriate strategic solutions. Financial feasibility was evaluated using investment analysis methods, including Net Present Value (NPV), Internal Rate of Return (IRR), and payback period calculations. Findings – The results indicate that the main challenges faced by CV Bersama Jaya are ineffective marketing strategies and insufficient human resource development. The company has not optimized social media utilization for marketing activities and customer engagement, while employee understanding of customer relationship management remains limited. The proposed development strategies include implementing new marketing strategies, improving customer engagement practices, restructuring the organization by adding employees, renewing production machinery, and developing financial and investment projections to support future growth. Originality/Value This research is original in combining operational, marketing, and human resource evaluations with financial feasibility analysis in a single business planning framework. The findings provide practical value by offering integrated development strategies supported by investment appraisal methods to guide managerial decision-making.